TEACHING ENGLISH TO EFL YOUNG LEARNERS THROUGH CHILDREN POETRY - Setiyani, Solis (2014)
The preliminary study revealed that EFL teachers never used children poetry as a learning material for EFL young learners. The teachers thought it was not relevant and demotivating. Such negative perspective and little interaction with poetry, hence, invested children with negative attitude toward this literary text. Whereas, as an interesting material, children poetry can promote a number of positive learning functions related to language ability, increasing motivation, and holistic children's development. The problems found actually can be solved by selecting suitable poetry and arranging appropriate instructions for EFL young learners. In brief, the study intends to: (1) explore the process of teaching English to EFL young learners through children poetry; and (2) investigate the EFL young learners' responses toward their English learning through children poetry. The study employs qualitative approach with exploratory research design. Nine sixth graders of two elementary schools in Bandung were selected as the research participants. The data was obtained by employing four techniques: non-participant observations, video recording, documents collection, and in-depth interviews. The data from all sources was coded; then, the description of research participants and several themes were generated for analysis. The findings revealed that, in fact, children poetry can be used as a language resource in EYL program. Here, the teacher played determining role as the organizer and the enabler. The young learners also considered children poetry and the instructions enjoyable. They shared their understanding to discover poetry meaning by being engaged to the three-way interactions. They were also involved in the thinking process, feeling expression, and knowledge about quality poetry. Employing children poetry in EFL teaching for young learners was found to be fulfilling their cognitive and language development, social and emotional need, and physical involvement. Therefore, the study recommends the decision makers and the teachers to include children poetry as one of learning materials in EYL program. For further research, the study suggests other researchers to continue and develop similar research in a formal context. Keywords: EFL young learners, children poetry, language-based approach, instructional interaction, children's responses